Syphilis acquired: an epidemiological review of cases in adults and elderly in the municipality of Porto Alegre/RS - Clós Mahmud, Ibrahim (2019)
Background and Objectives: It is known that acquired syphilis, in the “gaúcho” epidemiological scenario, is a disease of extreme importance due to its high prevalence and rise. From this, the following work aims to review the measures used in the care of adult and elderly patients diagnosed with acquired syphilis and its epidemiology in the city of Porto Alegre / RS. Contents: According to data published in 2016 by the Ministry of Health, the growth of syphilis infection in adults and elderly individuals is in great expansion in Brazil. Through the achievements of the elderly in the last decades, the prolongation of sexual life is a point worth highlighting, besides the incentive to socialization and the lack of information on sexual health. Conclusion: Sexually transmitted infections grow in these two publics and more effective preventive measures in the field of public health are needed. Keywords: Syphilis. Communicable Diseases. Public Health. Infectious Disease.